Development of a Literacy Leadership Model Based on Ki Hadjar Dewantara’s Leadership Trilogy at Tamansiswa College - Supriadi, Didi; Purbonuswanto, Welius; Maulida, Alfiatul (FKIP Universitas Lampung, 2025)
Abstract: Development of a Literacy Leadership Model Based on Ki Hadjar Dewantara's Leadership Trilogy at Taman Siswa College. Objectives: This study aimed to construct a structural model of literacy leadership grounded in Ki Hadjar Dewantara's leadership trilogy at Sekolah Taman Siswa. The research employed a quantitative methodology via a survey technique. Methods: The research was carried out from April to September 2024. The study was conducted at Sekolah Tamansiswa institutions in the Special Region of Yogyakarta. The participants in this study included the principal, vice principal, and teachers of Tamansiswa school in the Special Region of Yogyakarta. The sampling method employed was purposive sampling, with 116 respondents. The data gathering method employed a questionnaire, succeeded by quantitative descriptive analysis and model analysis utilizing the Structural Equation Model (SEM). Findings: The analysis results demonstrated that the Ki Hajar Dewantara leadership variable significantly and positively influences Literacy Leadership. Ki Hajar Dewantara's leadership elucidated literacy leadership by 64.7%. Ing ngarsa sung tuladha, as articulated by Ki Hajar Dewantara, underscores the significance of educators as exemplars, aligning with the notion of literacy leaders who are required to inspire and motivate others through tangible deeds. Ing madya mangun karsa constitutes a significant component of the Ki Hajar Dewantara Leadership Trilogy. Ing madya mangun karsa contributes to fostering an environment that promotes and sustains literacy growth. Literacy leaders must cultivate a literacy culture that empowers and fosters active engagement. Tut wuri handayani underscores the function of leaders as facilitators and motivators who offer assistance and guidance from a supportive position. Conclusion: The Ki Hajar Dewantara's leadership is proven to have a significant and positive influence on Literacy Leadership. The leadership approach based on Ki Hajar Dewantara's values directly contributes to improving the quality of literacy leadership. A literacy leader must be attuned to individual needs and offer suitable support to maximally enhance reading abilities. Keywords: literacy model, educational leadership, leadership trilogy, ki hadjar dewantara, taman siswa school.